Job involvement of male and female graduate engineers in South Africa - Von Hirschfeld, S D (Organisational Psychology, 2016)
The study investigated the job involvement of a sample of 125 graduate engineers in South Africa. In particular, whether gender differences existed in the level of job involvement, as well as in the factors influencing job involvement (N = 68 males; N = 57 females). The specific factors investigated were biographic variables and career anchors. The method used was the analytical survey method; three questionnaires were administered. These were: the Lodahl and Kejner (1965) Job Involvement Scale, Schein's (1982) Career Anchor Inventory and a biographic questionnaire. Questionnaires were sent to all female engineers who are registered with one of the professional engineering institutes, while the male sample was drawn from a variety of sources. Intercorrelation coefficients were calculated for all variables. Analyses of variance were performed to test for significant differences amongst male and females with respect to the variables and relationships measured and a stepwise multiple regression analysis was performed to identify predictors of job involvement by career anchors. No gender differences in level of job involvement were found. However, significant gender differences were found in the relative strength of four out of the nine career anchors measured. Social conditioning and expectations were proposed as the reasons for this. Further, significant differences were found with respect to the degree to which career anchors are related to job involvement for males and females. Contrary to conventional wisdom, being married and having children did not affect the job involvement of female engineers, while married men were more job involved than unmarried men. The study did not contribute greatly to the understanding of the dynamics of female job involvement, inasmuch as career anchors were found to explain only 8, 8% of the variance in job involvement scores. In contrast, career anchors were found to be significant predictors of job involvement for males. (38,8% of the variance explained). Implications of the results are discussed in terms of the alleviation of the skills shortage and organisational strategies such as the development of technical or specialist career ladders, job design and career counselling and career management skills for both males and females, are proposed. Further areas for research, especially into the dynamics of female job involvement, are suggested.